Investigation of low-temperature performances of hybrid catalysts with different chain length OHC reductants - Keskin, Zeycan (Environmental technology, 2022)
In the present work, NOx conversion efficiency of the hybrid catalysts at low temperatures was investigated. ANP-TVM and ANP-TVC-TVM hybrid catalysts for OHC-SCR performance were prepared by the impregnation method. The properties of catalysts were characterized by scanning electron microscopy (SEM), Brunauer-Emmett-Teller (BET) and X-ray diffraction (XRD) analyses. The NOx conversion ratios with real diesel exhaust gases were performed using oxygenated hydrocarbon reductants such as ethanol, propanol, n-butanol and n-penthanol. Performances of the hybrid catalysts at different engine loads and low temperatures were investigated. It was determined that ANP-TVC-TVM gave better results at all temperatures and loads. In general, the performance of ANP-TVC-TVM hybrid catalyst was superior with ethanol reductant except for at 1 kW engine load. The maximum NOx conversion ratio was 90.6% on the ANP-TVC-TVM hybrid catalyst with n-butanol at 1 kW engine load and 300°C